Coping Strategies being Practiced by the Breast Cancer Survivors before Receiving First Cycle of Chemotherapy - Sharma, Deeksha; Dutta, Monika; Kaur, Sukhpal; Yadav, Budhi Singh; Kumar, Krishan; Dahiya, Divya (Asian Pacific Journal of Cancer Care, 2021)
Objective: Breast cancer is the most common cancer among Indian females and chemotherapy is the most extensively used modality for these patients. Diagnosis of breast cancer is dreadful in itself and the initiation of chemotherapy causes stress and fear among patients. Breast cancer survivors (BCS) use different coping mechanisms to deal with these experiences and to handle these stressful events. The objective of this study was to assess the coping strategies being practiced by the BCS before receiving first cycle of chemotherapy. Method: This descriptive study was conducted on BCS attending Radiation Oncology and General Surgery OPD, PGIMER, Chandigarh from July 2018 to December 2019. Sixty two BCS were recruited using purposive sampling. Results: 51.7% participants were above 50 years of age, 56.5% had grade III breast cancer and 56.7% had left breast involvement. 62.9% were on neo-adjuvant chemotherapy and duration of confirmed diagnosis for 83.9% of them was less than a year. Most of the participants used positive coping strategies to overcome the stress related to diagnosis and chemotherapy. Out of the 46 coping activities participants retorted positive action for 31 coping activities whereas action was negative for 13 activities. Remaining two activities had equal number of positive and negative responses. Escape avoidance ‘hoped a miracle would happen’; ‘Wished that the situation would go away or somehow be over with’ were used by all the participants. Though not dominant, negative coping activities were still used by the participants to deal with stressful situations. Conclusion: BCS were predominantly using positive coping activities. In order to further increase this there is a need among medical professionals to make BCS aware and discourage the use negative coping behaviors. BCS can also be nudged to adopt positive coping styles by involving family and society in the provision of care.